Designing smart charge controller for the solar battery charging station (SBCS) - Ferdausi, Marufa (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.